2010
DOI: 10.1021/ie901685m
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Design of Calorific Value Adjustment Process using Process Simulators

Abstract: In this work, we present a solution procedure for design of a chemical process for effectively adjusting calorific values in an offshore regasification terminal. To tackle the technical and commercial issue in the liquefied natural gas (LNG) industry caused by differences of LNG calorific values between importing countries, many methods and configurations are being studied. This design problem is defined in two parts: a generalized disjunctive programming (GDP) problem with one objective and a multiobjective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Since sequential modular simulators, such as Aspen HYSYS, have process unit models precoded with their solution routines, they are simple to use and provide a straightforward solution strategy. Nevertheless, they have a major drawback in optimizations; it is difficult to obtain gradients to apply deterministic optimization methods, and if possible, it is difficult to apply deterministic optimization strategies because the simulation results slightly vary with repeated executions. This is mainly caused by the initial guess values for tearing streams and the tolerances required for the iterative converging procedures .…”
Section: Solution Proceduresmentioning
confidence: 99%
“…Since sequential modular simulators, such as Aspen HYSYS, have process unit models precoded with their solution routines, they are simple to use and provide a straightforward solution strategy. Nevertheless, they have a major drawback in optimizations; it is difficult to obtain gradients to apply deterministic optimization methods, and if possible, it is difficult to apply deterministic optimization strategies because the simulation results slightly vary with repeated executions. This is mainly caused by the initial guess values for tearing streams and the tolerances required for the iterative converging procedures .…”
Section: Solution Proceduresmentioning
confidence: 99%
“…Many studies have been reported on the development of linking process simulation with optimisation tools. For instance, Kim et al 14 reported the linking of optimisation problem of a caloric adjustment process between Aspen HYSYS and MATLAB via component object model (COM) interface. Another work by Al‐Sobhi and Elkamel 15 has successfully combined ASPEN Plus with a commercial optimisation software (i.e., LINGO) for profit maximisation in a natural gas processing and production network.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there are several works about the modeling of absorption heat pumps with analytical model [11,12] or with the combination of process simulations and optimization tools [14][15][16][17][18]. In addition, many mathematical models are developed for LiBr-H 2 O absorption heat pumps [19,20].…”
Section: Introductionmentioning
confidence: 99%